ANALISIS PENGGUNAAN WIND TOWER DAN SOLAR CHIMNEY SEBAGAI SOLUSI PENGHAWAAN ALAMI DI DAERAH ISTIMEWA YOGYAKARTA - M. Nur Amin S (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2016)
ABSTRACTThe objective of this paper to find solution of natural ventilation use wind tower and solar chimney based on windpotentials in Special Region of Yogyakarta. The method that was used was analyze wind tower and solar chimneymodel based on secondary data such as the result of documentation from The Meteorology, Climatology andGeophysics. The result of the analysis were (1)the most ideal dimension of wind tower with 6 m high,2 m long and1 m wide, while of solar chimney with 6 m high, 2 m long and 0,55 m wide. (2)the wind tower material usestyrofoam concrete while for solar chimney use steel/concrete with glaze for facade and head use aluminium.(3)the head direction of wind tower orientate south and southwest while head direction of solar chimney distancethe direction of wind tower head orientate north and northeast.Keywords: Model, Wind Tower, Solar ChimneyABSTRAKTujuan penulisan paper ini adalah untuk mengetahui solusi penghawaan alami menggunakan wind tower dansolar chimney berdasarkan potensi angin yang ada di Daerah Istimewa Yogyakarta. Metode yang digunakanadalah menganalisis model wind tower dan solar chimney dengan menggunakan data sekunder yang berupahasil dokumentasi Badan Meteorologi, Klimatologi dan Geofisika. Hasil analisis yang didapatkan yakni (1)dimensiyang paling ideal untuk wind tower adalah dengan tinggi 6 m, panjang 2 m dan lebar 1 m sedangkan untuk solarchimney adalah dengan tinggi 6 m, panjang 2 m dan lebar 0,55 m. (2)material penyusun wind tower berupa betonstyrofoam sedangkan untuk solar chimney berupa logam/beton dengan fasad berupa kaca dan headmenggunakan aluminium. (3)arah head wind tower menghadap selatan dan barat daya sedangkan arah headsolar chimney membelakangi arah wind tower yakni utara dan timur laut.Kata Kunci: Model, Wind Tower, Solar Chimney